Genetic heterogeneity of polydactyly in Maine Coon cats. Issue 12 (December 2020) - Hamelin, Alexia; Conchou, Fabrice; Fusellier, Marion; Duchenij, Bettina; Vieira, Isabelle; Filhol, Emilie; Dufaure de Citres, Caroline; Tiret, Laurent; Gache, Vincent; Abitbol, Marie
Objectives: Polydactyly has been described in two breeds of domestic cats (Maine Coon and Pixie Bob) and in some outbred domestic cats (eg, Hemingway cats). In most cases, feline polydactyly is a non-syndromic preaxial polydactyly. Three variants located in a regulatory sequence involved in limb development, named ZRS (zone of polarising activity regulatory sequence), have been identified to be responsible for feline polydactyly. These variants have been found in outbred domestic cats in the UK ( UK1 and UK2 variants) and in Hemingway cats in the USA ( Hw variant). The aim of this study was to characterise the genetic features of polydactyly in Maine Coon cats. Methods: Genotyping assay was used to identify the variant(s) segregating in a cohort of 75 polydactyl and non-polydactyl Maine Coon cats from different breeding lines from Europe, Canada and the USA. The authors performed a segregation analysis to identify the inheritance pattern of polydactyly in this cohort and analysed the population structure. Results: The Hw allele was identified in a subset of polydactyl cats. Sequencing of two regulatory sequences involved in limb development did not reveal any other variant in polydactyl cats lacking the Hw allele. Additionally, genotype–phenotype and segregation analyses revealed the peculiar inheritance pattern of polydactyly in Maine Coon cats. The population structure analysis demonstrated a genetic distinction between Hw and Hw -free polydactyl cats. Conclusions and relevance: Polydactyly in Maine Coon cats is inherited as an autosomal dominant trait with incomplete penetrance and variable expressivity, and this trait is characterised by genetic heterogeneity in the Maine Coon breed. Maine Coon breeders should be aware of this situation and adapt their breeding practices accordingly.